Quality control in early intervention centers for young children with special needs - Ealdama, Susan Janette G. (Education Quarterly, 1984)
This study aimed to identify what and how often quality control practices are implemented in Early Intervention (EI) centers. Focus group discussions (FGDs) among 22 participants yielded several aspects of early intervention in four domains: the child and the EI program; parent-professional collaboration; government, non-government, and community linkages; and legislation and societal values. Results were used in constructing a 50-item survey questionnaire, administered to 30 respondents working in 17 EI centers for different age groups. Results showed that almost all the EI centers had these daily activities: development of self-help skills, use of sensorial materials, parent-teacher consultations, and beginning reading, writing, and numeracy lessons. In general, the EI centers concentrate on direct instruction of the child but do not prioritize macro components such as implementation of accessibility laws. Recommendations include standardization of quality control in EI centers, especially the requirement of a transition plan upon exit from the EI program.